2015
DOI: 10.5271/sjweh.3520
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific association between night-work exposure and type-2 diabetes: results from longitudinal study of adult health, ELSA-Brasil

Abstract: This gender-specific analysis showed different patterns of association between night work and diabetes for men and women. Results suggest that the effect of exposure to night work appears to take longer to manifest itself among men, highlighting the greater chances of developing diabetes particularly among female night workers.Affiliation: National School of Public Health, Oswaldo Cruz Foundation -ENSP/FIOCRUZ, Brazil. Institutional address and email: Av.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
1
23
1
6
Order By: Relevance
“…Vimalananda et al 9 report similar estimate to Pan et al ,8 with BMI-adjusted estimate of 23% (1.23; 1.03 to 1.47) increase in diabetes incidence in African-American women working more than 10 years night shift (11% and 9%, for those working 3–9 and 1–2 years, respectively) compared with women never working night shift 9. A stronger association was detected among female civil servants in Brazil who had a 42% (1.42; 1.39 to 1.45) higher risk of diabetes after 20 years of night shift work, compared with those who had never worked night shift work 18. Our findings are consistent with the meta-analyses by Gan et al 6 who found that associations between shift work and diabetes are stronger in Europe (1.36; 1.05 to 1.73), than the USA (1.09; 1.03 to 1.14) and in Asia (1.07; 1.03 to 1.11), although this may be due to differences in study design as discussed above 8.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Vimalananda et al 9 report similar estimate to Pan et al ,8 with BMI-adjusted estimate of 23% (1.23; 1.03 to 1.47) increase in diabetes incidence in African-American women working more than 10 years night shift (11% and 9%, for those working 3–9 and 1–2 years, respectively) compared with women never working night shift 9. A stronger association was detected among female civil servants in Brazil who had a 42% (1.42; 1.39 to 1.45) higher risk of diabetes after 20 years of night shift work, compared with those who had never worked night shift work 18. Our findings are consistent with the meta-analyses by Gan et al 6 who found that associations between shift work and diabetes are stronger in Europe (1.36; 1.05 to 1.73), than the USA (1.09; 1.03 to 1.14) and in Asia (1.07; 1.03 to 1.11), although this may be due to differences in study design as discussed above 8.…”
Section: Discussionmentioning
confidence: 92%
“…In Vimalananda et al ,9 women were asked if they had ever worked a night shift (graveyard shift, from 00:00 to 8:00), and for how many years. Silva-Costa et al 18 require a minimum of four night shift per month to be classified as a night shift worker. Finally, Morikawa et al 12 compared day work only to two shift work (day and evening shifts) and three shift work (day, evening and night shift work).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Studies undertaken in the last few decades report an association between shift work and multiple chronic diseases, one of which is type 2 diabetes. [5][6][7][8][9][10][11][12][13] Shift work remains a common working schedule in certain sectors, including in the healthcare, utilities, food services, manufacturing, and transportation sectors. Approximately 21% of all workers in the European Union 14,15 are engaged in shiftwork, as are 28.7% of workers in the United States, 16 and 15-36% of workers worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…17 While epidemiological evidence of the association between shift work and type 2 diabetes risk is relatively sound, evidence pertaining to the gender differential of this association remains scarce and controversial. Based on the baseline data of a Brazilian Longitudinal Study of Adult Health (ELSA-Brazil) comprising 15,105 civil servants, a recent study by Silva-costa et al, 11 reported that the association between night work and diabetes was stronger among women [(odds ratio (OR) (1.42 95% confidence interval (CI)) (1.39-1.45)] than men [OR (95% CI)=1.06 (1.04-1.08)]. In addition, a 2013 population-based cohort study by Eriksson et al, 18 involved 3205 women and 2227 men in Sweden, and used patients aged 35-56 years.…”
Section: Introductionmentioning
confidence: 99%